DIGITAL MODELING OF THE HEAT TRANSFER PROCESS IN OIL POWER TRANSFORMERS IN OPERATION: Analysis of heat transfer processes occurring in oil power transformers in operation through digital modeling, identification of heat sources, and assessment of temperature distribution inside the transformer using mathematical and graphical models. As a result, it is planned to develop proposals for increasing the efficiency of the cooling system, ensuring reliability and reducing thermal stresses. - Mukhammadjonov, Mukhammadyusuf (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Digital modeling of heat transfer processes in oil power transformers is a very important tool for determining their thermal state and assessing their reliability. Based on the results obtained during the study, the following main conclusions were made: With the help of COMSOL Multiphysics, the heat distribution of a 1000 kVA transformer was determined. The temperature reached its highest level in the high-voltage winding zones (92°C), indicating the most dangerous areas inside the transformer. The efficiency of the cooling system is high, and the temperature in the lower parts is maintained in the range of 65-70°C. By increasing the radiator dimensions and oil circulation speed, it is possible to reduce the maximum temperature by 6-8°C. Based on the modeling results, specific technical recommendations for optimizing the design of the cooling system were developed. It is also possible to reduce thermal stresses by improving the design of cooling elements. 4. Based on the results of digital modeling, opportunities are being created for the development of real-time monitoring systems and remote control through temperature sensors and IoT devices. This leads to increased safety and service life during operation.